APLIKASI BIOPLASTIK DARI TEPUNG PORANG SEBAGAI KEMASAN MAKANAN - Fitriyana Fitriyana; Qhomaruddin Qhomaruddin; Mardhiyah Nadir (JURNAL TEKNIK KIMIA VOKASIONAL (JIMSI), 2022)
The use of plastic as packaging is inseparable from everyday life. Along with the increasing human attention to the environment, many studies have been carried out to find packaging materials as a substitute for synthetic plastics that are able to degrade naturally (bioplastics) from natural polymer materials such as starch, cellulose and fiber. The starch used is sourced from porang flour. The purpose of this study is to determine the effect of the use and characteristics of porang flour bioplastics as food packaging on the durability and quality of food during storage. This study made a bioplastic of porang flour by dissolving chitosan 1.5% (w/v) with 0.5% acetic acid then adding 2.5 g of porang flour, 3% glycerol (v/v) and aquades then heated to 80oC. Then it was molded and dried to a temperature of 60oC. The resulting bioplastics were applied to food, namely So Nice sausage. Food packaging conditions varied in open and closed places (without wrapping, plastic wrapping and bioplastics) observed for 8 days. The characteristics of the resulting bioplastics include water content of 60.20%, water absorption of 92.35%, water vapor permeability of 0.7391 g./h.m2 and biodegradation of 100% in 7 days. The results of visual observations showed that sausages began to break down on the second day (in the open) and the first day (on the closed place). Based on visual observations, bioplastics were not good at maintaining the durability and quality of food during storage.. Keywords : bioplastics, glycerol, food packaging, chitosan, porang flour